Mean and seasonal circulation of the south Indian ocean estimated by combining satellite altimetry and surface drifter observations - Peter, Benny Neettumkkara (2014)
The mean velocity field of south Indian Ocean has been derived by combining high resolution maps of sea level anomalies and the surface drifter data from the Global Drifter program from 1993 to 2012 with a resolution of 1/3 × 1/3 degrees in latitude and longitude. The estimated mean velocity field exhibits strong western boundary currents, zonal currents and eastern boundary currents. The Agulhas Current shows a velocity of above 1.5 m s-1 at around 35°S. The distribution of energy associated with the fluctuating motion and the mean flow illustrates that mesoscale variability are particularly relevant in the Mozambique Channel, south of Java and around 40°S. Advection of mesoscale features along the western boundary is evident in the distribution of eddy fluxes. The long-term average monthly surface velocity field exhibits large variations in surface currents. The most change is observed in the South Equatorial Current which shows spatial and temporal variations